Sumbangan Arkeologi dalam Mewujudkan Solidaritas Sosial dan Integrasi Bangsa - Gunadi Kasnowihardjo (Balai Arkeologi Sumatera Utara, 2010)
AbstractTo be utilized, as an unrenewable resources, the archaeological resources must be conserved well. It has the advantages and value added such as environmental conditions or ecological, aesthetic and architectonic, historical, geological etc. in addition, an internal potentials as noted above, archaeological resources also have an external potential, which can be utilized by other sectors.